Order effects of high-intensity intermittent and strength exercise on lipoprotein profile - Diniz, Tiego Aparecido [UNESP]; Inoue, Daniela Sayuri [UNESP]; Rossi, Fabricio Eduardo [UNESP]; Panissa, Valéria Leme Gonçalves; Monteiro, Paula Alves [UNESP]; Lira, Fabio Santos [UNESP] (Springer Nature, 2016)
Purpose: To compare the effects of the order of concurrent exercise (endurance plus strength or strength plus endurance) on lipoprotein profiles in men. Methods: After the evaluation of maximum strength (one repetition maximum—1RM) in the half-squat and of aerobic fitness (maximal velocity in treadmill incremental test), 11 physically active male subjects underwent two randomized sessions composed of four sets of half-squat strength exercises until exhaustion (at 80 % of 1RM) and a 5-km run high-intensity intermittent exercise (1:1 min at Vmax), performed in different orders: (1) strength plus run (S-A) and inverse order, and run plus strength (A-S). Blood samples were collected before and immediately after the first exercise (Post-1) and after the second exercise (Post-2) in the intra-session sequence. Serum was analyzed for total cholesterol (TC) and its ratio, HDL-c and LDL-c, and triacylglycerol (TAG). Results: There were effects of condition for TC, LDL-c, and TC/HDL, with greater values in the AS than SA (p < 0.001 for all). For the delta analysis, there was an interaction effect for TAG, with greater delta-1 S-A than delta-1 A-S (p = 0.035), and higher delta-1 S-A than delta-2 S-A (p = 0.001); for LDL-c, with higher delta-1 S-A values than delta-2 S-A (p = 0.010); and for TC, with higher delta-1 S-A values than delta-2 S-A (p = 0.038). Conclusion: We conclude that there are no differences between the order of acute high-intensity intermittent run plus strength exercises regarding modulation of the lipoprotein profile in healthy, physically active men.
Keywords: Aerobic exercise; Lipoprotein; Strength exercise